Vanguard Total Index: Conceptual Writing, Information Asymmetry, and the Risk Society. - Stephens, Paul (Contemporary Literature)
An essay is presented on conceptual writing's appropriation strategies in literary works. It examines the role of conceptual writing as poetic appropriation strategies for poets and writers. It highlights the impacts of concerning matter of privacy, authenticity, identity and information asymmetry. It also mentions the structure of information systems considering the indexical form and bureaucratic forms as linguistic forms of large quantities.